Choosing Wisely Italy, and the role of doctors in containing the climate emergency (Dermatology Reports, 2023)
The philosopher of science, Telmo Pievani, in his beautiful and passionate presentation on 30 September 2023, at the conclusion of the 60th National Congress of the Italian Association of Hospital Dermatologists (ADOI) held in Vicenza, reminded us with simple words and concrete examples of the devastating impact of human behavior on the environment and biodiversity, highlighting the growing deterioration of the delicate natural balances that preserve terrestrial ecosystems and with them life on our planet [...]